PROGRAM PENINGKATAN KREATIVITAS DAN INOVASI ANAK MUDA MELALUI EDUKASI EKONOMI KREATIF DAN PENGEMBANGAN HOBI - Haris Fikrotul Alimi; Lintang Anggraeni; Amah; Mudzakir (Abdi Jurnal Publikasi, 2026)
This Community Service Program (PKM) aims to promote the enhancement of creativity and innovation among young people through creative economy education and the development of their personal hobbies. This activity is motivated by the relatively low level of awareness among youth in utilizing their hobbies as economically valuable opportunities. Through an educational and participatory approach, this program was implemented in the form of socialization, training, and interactive educational sessions that actively involved participants. The materials covered included an introduction to the creative economy, the importance of creativity and innovation, as well as methods to identify and develop hobbies into simple business opportunities.The results of the activity indicate an improvement in participants’ understanding of the concept of the creative economy, along with increased motivation to develop their personal potential. Participants began to realize that simple ideas derived from their hobbies can serve as an initial step in creating business opportunities. Therefore, this program is expected to have a positive impact in fostering independence and a creative mindset among young people.